p53 Modulates Radiosensitivity in Head and Neck Cancers—From Classic to Future Horizons - Camil Ciprian Mireștean; Roxana Irina Iancu; Dragoș Petru Teodor Iancu (Diagnostics, 2022)
p53, initially considered a tumor suppressor, has been the subject of research related to cancer treatment resistance in the last 30 years. The unfavorable response to multimodal therapy and the higher recurrence rate, despite an aggressive approach, make HNSCC a research topic of interest for improving therapeutic outcomes, even if it is only the sixth most common malignancy worldwide. New advances in molecular biology and genetics include the involvement of miRNA in the control of the p53 pathway, the understanding of mechanisms such as gain/loss of function, and the development of different methods to restore p53 function, especially for HPV-negative cases. The different ratio between mutant p53 status in the primary tumor and distant metastasis originating HNSCC may serve to select the best therapeutic target for activating an abscopal effect by radiotherapy as a “booster” of the immune system. P53 may also be a key player in choosing radiotherapy fractionation regimens. Targeting any pathway involving p53, including tumor metabolism, in particular the Warburg effect, could modulate the radiosensitivity and chemo-sensitivity of head and neck cancers.